Íleo terminal de pacientes submetidos à colonoscopia: aspectos endoscópicos, histológicos e clínicos - Melo, Marcelo Maia Caixeta de (2007)
The ileum is approximately the most distal three-fifths of the small intestine and is responsible for digestion and the absorption of foods. The diagnosis of diseases that affect this segment can be achieved by clinical evaluation and complementary examinations. Colonoscopy, not only allows macroscopical analysis, but also enables biopsies to be carried out for histological evaluation. Objective: The objective of this research was to study the terminal ileum of patients submitted to colonoscopy in respect to: 1) correlation of endoscopic and histological parameters; 2) compatibility between the initial histological results evaluation and a review of slides; 3) the chance of individuals with normal ileoscopy and abdominal pain and/or chronic diarrhea presenting with histological alterations. Casuistic and Method: Patients submitted to colonoscopy for varying reasons were prospectively studied. During this examination 47 (42.3%) male and 64 (57.7%) female patients, with ages ranging between 14 and 82 years old (mean 51.6 ? 15 years), were selected with the terminal ileum mucous smooth and without enanthema at endoscopic examinations. Biopsies of the ileal mucosa were obtained for these individuals with the slides being routinely examined during data collection and later reviewed. Results: The correlation between patients with normal xiii ileoscopy and histologically normal ileum was 34.2%. When patients with histologically normal ileum and mild ileitis were analyzed, the correlation was 99.1%. The agreement between the initial histological evaluation and review of slides in respect to normal ileum and mild or moderate ileitis according to the Kappa test was 0.10 (poor agreement). Considering the normal ileum together with mild ileitis and moderate ileitis Groups, the agreement was 0.21 (fair agreement). In patients with normal ileoscopy and abdominal pain and/or chronic diarrhea, the chance of presenting histological alterations by Odds Ratio calculation, was 2.5 times higher than for asymptomatic individuals or those with other symptoms. Conclusions: In patients with the terminal ileum mucosa smooth without enanthema, the correlation between endoscopic and histological findings was high. The concordance between the initial histological results evaluation and the review of slides was not good. The chance of individuals with normal ileoscopy and abdominal pain and/or chronic diarrhea, presenting histological alterations was greater than for asymptomatic individuals or those with other symptoms.